Legal Aspects of Occupational Health and Safety in Healthcare Facilities - Suparna, Ketut (Westscience Press, 2025)
Occupational Health and Safety (OHS) is a fundamental legal and ethical mandate designed to protect workers, especially in high-risk environments such as healthcare facilities. Despite the existence of a solid legal framework in Indonesia—including Law No. 1 of 1970 and Ministry of Health Regulations No. 66/2016 and No. 52/2018—national data reveal a continued rise in workplace accidents and occupational diseases, with needlestick injuries (NSIs) representing a prominent and alarming hazard. This study investigates the legal and ethical dimensions of OHS implementation in healthcare service facilities, analyzing systemic gaps between regulatory provisions and practical enforcement. Factors such as high workload, lack of safety-engineered devices, underreporting of incidents, and inadequate regulatory oversight contribute to persistent occupational risks. Ethically, the ongoing prevalence of avoidable incidents like NSIs raises serious questions about the institutional responsibility to uphold principles of non-maleficence, justice, and professional duty of care. The study concludes with legal and ethical recommendations to enhance enforcement mechanisms, bridge compliance gaps, and build a holistic safety culture in healthcare settings.